Land use, flooding regime, and seasons differentially shape composition of beetle species in a semi-arid highland floodplain in Central Kenya - Jane M. Macharia; Mathias Becker; Helida Oyieke; Kai Behn (International Journal of Tropical Insect Science, 2026)
Biodiversity is threatened globally by human-mediated alteration of natural environment. This includes East African wetland ecosystems that are subject to agriculture expansion and intensification. Monitoring of biodiversity is crucial to understand and mitigate biodiversity losses. Beetles, while rarely studied, are potentially useful bioindicators due to their sensitivity to environmental changes. Our study aimed at investigating the influence of land use regimes (cropland, fallow, grazing land, pristine), as well as flooding regimes and seasonality on the abundance, composition, diversity, and occurrence of beetle species in the Ewaso Narok swamp, Kenya. Using pitfall traps and sweep nets over two years (2015–2016) in 42 plots each of six sampling dates, we recorded 2,145 beetles (20 families, 179 species). Conversely to our hypothesis, we only found weak effects of land use on abundance, diversity and species composition. Seasons, and individual sampling dates were more important, partly due to varying rainfall prior to the sampling. Heavy rainfall decreased abundance of ground-dwelling beetles, particularly in the wettest zone. Regarding individual species, most occurred across all land uses and did not show much specificity. However, among ground-dwelling beetles, some species demonstrated significant associations with land use intensity. For instance, disturbance tolerant Tenebrionids such as Zophosis abyssinica and Gonocephalum simplex were associated with high land use intensity (cropland/fallows), while predatory Staphylinid Philonthus circumcinctus was associated with grazing lands. Hence, selected species may act as bioindicators and may represent “winners” and “losers” of land transformations. These results support biodiversity monitoring and future wetland use planning.